Matematik Öğretmeni Adaylarının Dijital Oyun Tasarlama Deneyimleri, Görüş ve Değerlendirmeleri: Draw Your Game Örneği. - ALDEMİR ENGİN, Ruhşen (Journal of Social Sciences Research / Sosyal Bilimler Araştırmaları Dergisi, 2023)
The aim of this research is to examine the opinions of secondary pre-service mathematics teachers by giving them an experience of designing digital games and to evaluate the games they create. Case study, which is one of the qualitative research designs, was used in the research. Participants were 39 sophomore pre-service teachers who were studying at a state university. The data were obtained from semi-structured interview form consisting of seven questions and digital games designed by the participants. The data were analyzed by content analysis. As a result of the research, it was determined that pre-service teachers liked drawing, designing and playing their own games the most. It was determined that they had problems due to the fact that the colors were not perceived correctly in the game. The ease of use of the touch screen was expressed as an advantage, and the undesirable result when accidentally touching the screen was expressed as a disadvantage. While preparing the game, the participants aimed to learn by having more fun, to keep the subject in mind and to simplify the subject. They stated that the game is fun and memorable when used in mathematics education as advantages, game addiction and going out of the game's purpose as disadvantages. It has been observed that the designed games were mostly associated with the secondary school level, the red and black elements were used extensively in the games, and the destruction games were designed more. In addition, the time to complete the games and the aims of the games are presented.